2021
DOI: 10.1055/a-1422-3376
|View full text |Cite
|
Sign up to set email alerts
|

Acute Response of Sclerostin to Whole-body Vibration with Blood Flow Restriction

Abstract: Blood flow restriction may augment the skeletal response to whole-body vibration. This study used a randomised, crossover design to investigate the acute response of serum sclerostin and bone turnover biomarkers to whole-body vibration with blood flow restriction. Ten healthy males (mean±standard deviation; age: 27±8 years) completed two experimental conditions separated by 7 days: (i) whole-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 56 publications
(81 reference statements)
0
1
0
Order By: Relevance
“…Different BFR methods (e.g., cuff pressure, cuff width and BFR type) result in different hemodynamics ( Neto et al, 2017a ; Zhang et al, 2022 ), which may have different effects on bone adaptations. Gapper et al (2021) found that there was no difference in the acute effects of LI-BFR training with 110 mmHg pressure versus LI training on bone metabolism among young adults. The most likely reason is that the cuff pressure of 110 mmHg may not be sufficient to elicit any osteocytic response.…”
Section: Discussionmentioning
confidence: 77%
“…Different BFR methods (e.g., cuff pressure, cuff width and BFR type) result in different hemodynamics ( Neto et al, 2017a ; Zhang et al, 2022 ), which may have different effects on bone adaptations. Gapper et al (2021) found that there was no difference in the acute effects of LI-BFR training with 110 mmHg pressure versus LI training on bone metabolism among young adults. The most likely reason is that the cuff pressure of 110 mmHg may not be sufficient to elicit any osteocytic response.…”
Section: Discussionmentioning
confidence: 77%